Legal mechanism for protecting the rights and interests of entrepreneurs (Journal of actual problems of jurisprudence, 2021)
The authors have made an attempt to comprehensively study the problems of ensuring the rights and freedoms of businessmen. We are talking about state measures to protect the rights of businessmen. Comprehensive measures to support small and medium-sized businesses are provided by law in the Republic of Kazakhstan.  In the context of the pandemic, the state canceled annual inspections of the activities of businessmen, introducing a moratorium. As you know, a three-year moratorium on inspections of small and microenterprises has been introduced in the Republic of Kazakhstan since 2020. This became an effective measure to protect businesses from government interference in their activities, which allowed individual entrepreneurs to build a successful business in difficult conditions. Civil scientists have been studying the legal mechanism for protecting the rights and interests of entrepreneurs for many years. Great importance is attached to mediation, pre-trial procedure for the consideration of various complaints and disputes. The education and awareness of the population, as well as the values of civil society: freedom, comprehensive development of the individual, the ability to protect their rights and comply with duties, should fulfill an enduring value in this. Do not forget about subsidies and benefits that can significantly reduce the tax burden for businessmen.Key words: entrepreneurial activity, business, pre-trial procedure, mediation, supervision, monopolies, antimonopoly regulation, protection mechanism, legitimate interests, legal means.